Changes in Celtic consumption: Roman influence on faunal-based diets of the Atrebates - Frey, Alexander (My University, 2016)
This study addresses cultural impacts of the Roman Empire on the British Celtic group, the Atrebates. The Atrebates held large portions of land in southern Britain, and upon Roman invasion in A.D. 43, became a client kingdom of the Roman Empire. With Roman rule also came Roman animal husbandry and consumption habits, reflected in archaeological faunal remains. To better understand this dietary transition, 23 faunal datasets were analyzed from within and around the capital city of Calleva Atrebatum, spanning from the pre-Roman Britain Iron Age to the post-Roman Saxon Age. In the analysis, published Number of Individual Specimens (NISP) and Minimum Number of Individuals (MNI) values were assessed to examine changes in the prominence of sheep, pigs, and cattle over time. This research demonstrates the pervasive impact of the Roman Empire on populations with whom they interacted, changing not only governing bodies, but also dietary practices.
Keywords: Archaeology--methodology; Archaeology and history; Archaeology